Training Prescription Guided by Heart Rate Variability Vs. Block Periodization in Well-Trained Cyclists. Issue 6 (June 2020) - Javaloyes, Alejandro; Sarabia, Jose M.; Lamberts, Robert P.; Plews, Daniel; Moya-Ramon, Manuel
Abstract : Abstract: Javaloyes, A, Sarabia, JM, Lamberts, RP, Plews, D, and Moya-Ramon, M. Training prescription guided by heart rate variability vs. block periodization in well-trained cyclists. J Strength Cond Res 34(6): 1511–1518, 2020—Predefined training programs are common place when prescribing training. Within predefined training, block periodization (BP) has emerged as a popular methodology because of its benefits. Heart rate variability (HRV) has been proposed as an effective tool for prescribing training. The aim of this study is to examine the effect of HRV-guided training against BP in road cycling. Twenty well-trained cyclists participated in this study. After a preliminary baseline period to establish their resting HRV, cyclists were divided into 2 groups: an HRV-guided group and a BP group, and they completed 8 training weeks. Cyclists completed 3 evaluations weeks, before and after each period. During the evaluation weeks, cyclists performed: (a) a graded exercise test to assess V[Combining Dot Above]O2 max, peak power output (PPO), and ventilatory thresholds with their corresponding power output (VT1, VT2, WVT1, and WVT2, respectively) and (b) a 40-minute simulated time-trial (40 TT). The HRV-guided group improved V[Combining Dot Above]O2 max ( p = 0.03), PPO ( p = 0.01), WVT2 ( p = 0.02), WVT1 ( p = 0.01), and 40 TT ( p = 0.04). The BP group improved WVT2 ( p = 0.02). Between-group fitness and performance were similar after the study. The HRV-guided training could lead to a better timing in training prescription than BP in road cycling.